Image of a horse as a symbol of ethnic identity (on the example of Kazakh and Tuva theatres) (Journal of Philosophy Culture and Political Science, 2024)
The article is devoted to the problem of cultural and ethnic identity in the national theatres of Kazakhstan and Tuva. In the national theatre the issue of socio-cultural ties is provided in theatrical performances through the manifestation on stage of cultural and national values, meanings and values as a reflection of ethnic identity, aesthetic and moral ideals of the people. Modern world theatre is a potential place of cultural forms reproduced by stage artists, offering to look through the eyes of the contemporary here and now, what we are today, what processes are taking place in the ethno-cultural society. The works of the authors of national theatres, as subjects of indigeneous culture, represent the presentation of cultural symbolic images, in which the ethnic identity of the people is reproduced. And in this connection, the question is raised how in modern conditions the ethnic is expressed in the national theatres of Kazakhstan and Tuva.The aim of the work is a comparative analysis of the symbolic image of the "horse" in the construction of the picture of the world in the national performances of the theatres of Kazakhstan and Tuva.The novelty of the study lies in the fact that the consideration of the concept of a "horse" as a symbolic image of cultural and ethnic identity in Kazakh and Tuvan culture in the context of a theatrical performance has not been the subject of cultural analysis. The theoretical and methodological basis of the article are the works of foreign, Kazakh (A.Sh. Mirzabekova, 2006), Russian (V.N. Badmaev, 2005,) and Tuvan scholars (Ch.K. Lamazhaa, 2018) who studied theproblems of national identity, as well as the works of Kazakh and Tuvan theatre scholars, philologists, and cultural scientists.The source base is theatre productions: the Kazakh play "Kulager" (directed by Farhad Moldagaliev, Kazakhstan) and the Tuvan play "Egil, ezhim, egil!" (directed by Alexey Oorzhak, Tuva). (directed by Alexei Oorzhak, Tyva).On the basis of the cultural analysis of the image of the horse, the authors of the article substantiated the concept of "horse" as a symbol of freedom and independence in the theatrical art of Kazakhstan and Tuva", revealed the symbolic image of "horse" in the Kazakh performance, reflecting the ethnic identity and traditional culture of this people, conducted an analysis of the image of "horse" in the national drama of Tuvinians as a cultural element that ensures the preservation and transmission of traditional values of this people.Keywords: horse image, traditional culture, ethnic identity, performance, Tuva, Kazakhstan